2020
DOI: 10.32601/ejal.775799
|View full text |Cite
|
Sign up to set email alerts
|

Promoting extended student talk in an EFL classroom

Abstract: This study aims to analyze the way one EFL teacher maintains and promotes extended student talk in an EFL Listening and Speaking Course at tertiary level via conversation analytic perspective. Promoting extended student turns is one of the main goals of meaning and fluency contexts in language classroom discourse (Seedhouse, 2004), thus, it is of quite importance to study extended student talk in a microanalytic and detailed way. The data were collected from an EFL class at a private university in Turkey. List… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
(82 reference statements)
0
4
0
Order By: Relevance
“…Baluyos, Rivera, and Baluyos (2019) asserts that Indonesia's biggest issues is that despite f receiving high enrollment, its quality has not improved. It is mainly because of this education system where teachers' creativity in classrooms is starved to death (Esia-Donkoh & Baffoe, 2018;Gezegi̇n & Melike, 2020;Gümüşok & Balikçi, 2020). If teachers are motivated by their internal urge to teach, they cannot motivate students to be independent.…”
Section: Introductionmentioning
confidence: 99%
“…Baluyos, Rivera, and Baluyos (2019) asserts that Indonesia's biggest issues is that despite f receiving high enrollment, its quality has not improved. It is mainly because of this education system where teachers' creativity in classrooms is starved to death (Esia-Donkoh & Baffoe, 2018;Gezegi̇n & Melike, 2020;Gümüşok & Balikçi, 2020). If teachers are motivated by their internal urge to teach, they cannot motivate students to be independent.…”
Section: Introductionmentioning
confidence: 99%
“…Looking at an EAP context, Demirkol et al (2021) indicated that giving speeches and asking and answering questions in conferences were the most difficult task for undergraduate learners in EMI universities. In addition to those studies that had a more experimental nature, for instance, looking at the role of extensive reading (Yakut, 2020), the use of Pecha Kucha technique (Solmaz, 2019), the use of L1 (Yüzlü & Atay, 2020), as well the effect of pressured online planning (Tuzcu & Yalçın, 2020) on L2 learners’ speaking and pronunciation, researchers have also adopted a more naturalistic approach to examine the ways in which EFL teachers promoted extended student talk (Gümüşok & Balıkçı, 2020) and provided oral corrective feedback (Ölmezer-Öztürk & Öztürk, 2016). Based on natural classroom observations, Kemaloğlu-Er and Özata (2020), for instance, revealed codeswitching in group work to be a builder of solidarity and a means of task achievement and interactional fluency.…”
Section: Classroom Processes and Instructional Practicesmentioning
confidence: 99%
“…In the presence of this dilemma, there has been a serious loss of cultural understanding among students in Indonesia, as a result of which, students are suffering from identity crisis. Islamic cultural understanding is the basic ingredient for any policy development which aims at integrating Islamic education in the national curriculum (Alsharari, 2017;Gümüşok & Balikçi, 2020;Henry, 2020). Islamic Education is vital in development of young leaders and their training on the Islamic model.…”
Section: Introductionmentioning
confidence: 99%